Impaired cerebrospinal fluid circulation and cerebral lymphatic drainage in a rat model of chronic hydrocephalus - Back, Dong Bin; Choi, Bo-Ryoung; Kwon, Kyoung Ja; Choi, Dong-Hee; Shin, Chan Young; Lee, Jongmin; Kim, Hahn Young (Frontiers in Molecular Neuroscience, 2025)
The cerebrospinal fluid (CSF) not only protects the brain but also maintains homeostasis by removing metabolic waste produced by brain activity. This study hypothesizes that chronic CSF circulatory dysfunction, such as chronic hydrocephalus or normal pressure hydrocephalus (NPH), may be a critical condition in neurodegenerative diseases associated with metabolic waste accumulation. To investigate the CSF circulation and cerebral lymphatic drainage in a rat model of chronic hydrocephalus induced by kaolin injection, we performed time-dependent evaluations of intraparenchymal injection of tracers as well as intraventricular injection of Evans blue. The study systemically evaluated the dysfunction of CSF circulation and lymphatic drainage in the brain from various perspectives, including the glymphatic system, transependymal CSF flow, subarachnoid CSF flow, meningeal lymphatic drainage, and peripheral lymphatic drainage to deep cervical lymph nodes. The results indicated delayed CSF circulation, including glymphatic system, and cerebral lymphatic drainage in the kaolin-induced chronic hydrocephalus model. Based on these findings, our research indicated that dysfunction of CSF circulation, as observed in conditions such as chronic hydrocephalus or NPH, may act as an initiating or exacerbating factor in neurodegenerative diseases. This can lead to the accumulation of metabolic waste, as seen in Alzheimer’s disease. Our research can help identify risk factors and provide insight into the underlying pathophysiology of neurodegenerative diseases, which may lead to the development of novel therapeutic strategies.